FREQUENCY OF POST-TONSILLECTOMY HAEMORRHAGE FOLLOWING TONSILLECTOMY WITH BIPOLAR DIATHERMY-AN EXPERIENCE AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Shah, Shahid A.; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2004)
Background: Tonsillectomy remains one of the most common surgical procedures performed in the world. Various techniques have evolved over the years. One of the most significant complications is postoperative hemorrhage. There is a general perception of increased frequency of PTH with the electro-cautery technique. A prospective study was designed to determine the frequency of post-tonsillectomy haemorrhage (PTH) following tonsillectomy with bipolar diathermy at ENT department, Ayub Medical College & Teaching Hospital, Abbottabad. Method:246 patients of varying ages and both sexes were operated by the same consultant using bipolar diathermy, during the period of April'2001 to March'2003. All the patients had antibiotic prophylaxis and analgesia on regular basis. Patients were hospitalized for 24-48 hours and were reviewed after one week. Results: 9 (3.6%) patients presented with PTH. These presented between day 3 and 11. Four (1.6%) presented with active bleeding, 3 (1.2%) presented with clot in the tonsillar fossa and 2 (0.8%) had a history of bleeding per-orally at home but did not have evidence of bleeding on arrival. All the patients were hospitalized and treated with a broad spectrum intravenous antibiotic, parenteral analgesia and intravenous fluids. None of the patients needed surgical intervention. Conclusion: Tonsillectomy with bipolar diathermy doesn't carry risk of PTH different from other standard techniques. It has the added benefit of minimal per-operative bleeding which bears significance in pediatric population. However adequate training in its use is mandatory to avoid thermal damage to the tissues. Key words: Tonsillectomy, post-tonsillectomy haemorrhage, bipolar diathermy